MOLECULAR CHARACTERIZATION, PHYTOCHEMICALS SCREENING, AND MOLECULAR DOCKING OF CARDAMOM (Wurfbainia compacta), AND SAMBILOTO (Andrographis paniculata) AGAINST COVID-19 - Kurniawati, Mufida Budi; Budiharjo, Anto; Kusumaningrum, Hermin Pancasakti; Ferniah, Rejeki Siti (BRIN - Badan Riset dan Inovasi Nasional, 2024)
Cardamom and Sambiloto are phytopharmaceutical plants that produce phytochemical compounds that have the potential to be used to increase immunity against COVID-19. because they contain carotenoids, phenols, anthocyanins, saponins, alkaloids and steroids. This research aims to obtain the molecular characteristics of Cardamom and Sambiloto plants from the Gunungpati area, Semarang by ITS primer, testing phenolic phytochemicals, tannins, flavonoids, saponins and alkaloids followed by molecular docking tests with the 6WX4 protein. SARS-CoV-2. Molecular characterization results show that Cardamom and Sambiloto are similar to Wurfbainia compacta MF802556.1 (100%) and Andrographis paniculate LC646073.1 (84.47%). The results of the phytochemical test screening showed that both plants contain flavonoids. Molecular docking tests were carried out with the compounds Quercetin, Avicularin, Naringenin, 5-hydroxy-7,8,2',5' tetramethoxyflavone, and Retinoic Acid. Retinoic Acid as a test ligand has the greatest potential in inhibiting the 6WX4 protein in the SARS-CoV-2 virus with a binding affinity value of -7.28 and RMSD 0.00.